Community Understanding In The Development of Nglinggo Tourism Village, Kulon Progo Regency, Special Region Yogyakarta - Hermanto, Sugeng; Hidayah, Nurdin; Suherlan, Herlan (Politeknik Negeri Bandung, 2023)
This study aims to understand in-depth and comprehensively how the Nglinggo Tourism Village community understands tourism development in its place. This study has used a qualitative approach with a case study design. The data collection techniques used were direct observation of the location of the locus that the researcher wanted to examine, observing events, incidents, poses, and conditions along with a list that needed to be observed in Nglinggo Pager Harjo Tourism Village, as well as conducting interviews with key informants who were involved and experienced all activities relating to the Tourism Village in Nglinggo Pager Harjo. The study concluded that people have begun to understand tourism as an industry that significantly influences improving people's welfare regarding human resources, community potential, and physical development. Community understanding of tourism development can be assessed and understood by the local community. In addition, it can also be concluded that tourism has not negatively influenced the norms, laws, and customs of the local community.